2020
DOI: 10.3390/ijtpp5040027
|View full text |Cite
|
Sign up to set email alerts
|

Design and Commissioning of a Combustor Simulator Combining Swirl and Entropy Wave Generation

Abstract: Modern aero-engine combustion chambers burn a lean and premixed mixture, generating a turbulent flame which involves large heat-release fluctuations, thus producing unsteady temperature phenomena commonly referred to as entropy waves (EWs). Furthermore, to enhance the fuel air mixing, combustion air is swirled, leading to vorticity disturbances. These instabilities represent one of the biggest challenges in gas turbine design. In this paper, the design and testing of a novel entropy wave generator (EWG) equipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Finally, an unavoidable drawback of the employed injector is the significant wake released by the stem. However, previous experimental campaigns in a wind tunnel have shown that the wake is completely reabsorbed at stator leading edge [20]. As such, the aforementioned flow features of the generated swirl make the generated vortex comparable to what documented in literature [16,17,25,26].…”
Section: Generated Disturbancesupporting
confidence: 74%
See 4 more Smart Citations
“…Finally, an unavoidable drawback of the employed injector is the significant wake released by the stem. However, previous experimental campaigns in a wind tunnel have shown that the wake is completely reabsorbed at stator leading edge [20]. As such, the aforementioned flow features of the generated swirl make the generated vortex comparable to what documented in literature [16,17,25,26].…”
Section: Generated Disturbancesupporting
confidence: 74%
“…These authors agree that the higher the frequency, the higher is the EW dissipation caused by diffusion and dispersion inside the duct from the combustor to the turbine inlet. Therefore, an EW is expected to preserve a significant magnitude at turbine inlet only at low frequencies: 10 and 110 Hz seem to match the previous statement, as also showed in Notaristefano and Gaetani [20].…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations